Maintenance work for heritage buildings in Malaysia: owners’ perspectives - Zolkafli, Umi Kalsum; Zakaria, Norhanim; Mohammad Mazlan, Aina; Ali, Azlan Shah (Emerald, 2019)
Purpose: The purpose of this paper is to establish the impacts of good maintenance work for heritage buildings in Malaysia. This purpose is achieved through identifying factors that lead to the lack of maintenance of heritage buildings, establishing strategies to overcome the lack of maintenance of heritage buildings and analyzing the impact of good maintenance work on heritage buildings in Malaysia. Design/methodology/approach: A quantitative method was employed for this study to identify the variables that most influence the maintenance of heritage buildings in Malaysia. The respondents were the owners of the heritage buildings in Peninsular Malaysia. There were 65 owners of heritage buildings identified from the official website of the Department of National Heritage, Ministry of Tourism and Culture, Malaysia. Simple random sampling was used to obtain the sample size of the targeted respondent. A total of 56 questionnaire surveys were distributed to the owners of heritage buildings. In total, 37 respondents returned the completed questionnaires, resulting in a response rate of 66 percent. The data were analyzed by Descriptive Statistics using Statistical Package for the Social Science software version 20. Findings: Results show that the factors that lead to the lack of maintenance of heritage buildings are limited finance, the absence of maintenance guideline and ill-defined maintenance policy. The strategies to overcome the problem include providing a financial budget by the respective authorities, establishing a standard maintenance guideline and revising the existing policy. Research limitations/implications: The paper is limited to the identification of factors that lead to a lack of maintenance and strategies to overcome the problem for the heritage buildings in Malaysia. The respondents are the owners of heritage buildings in Malaysia. The focus is given to them due to the fact that it will help them in understanding the importance of managing and operating for their buildings. Practical implications: The results offer value-added information to building managers who are responsible for maintaining heritage buildings. Findings show that good maintenance work on heritage buildings can enhance the value and safety of the building as well as preventing heritage buildings from deteriorating. Social implications: The quality of maintenance could be enhanced by focusing on the important variables that affect the quality of maintenance works of heritage buildings. Originality/value: Limited studies had been carried out in the context of the maintenance of heritage buildings, especially in Malaysia.